Metode Pelayanan Pendidikan Bagi Anak Tunanetra Di Slb Negeri Keleyan - Putri Nihayatut Thoyibah; Nova Estu Harsiwi (Universitas Maritim AMNI Semarang, 2024)
This research was conducted at SLB Negeri Keleyan which aims to find out how to provide educational services for children with visual impairments. This type of research uses a qualitative method with a descriptive approach and uses data collection techniques including observation, interviews and documentation. SLB Negeri Keleyan provides various methods to provide the best services for children with special needs, especially for those with visual impairments. One commonly used method is through audio or voice, which helps improve a child's vocabulary. In addition, the curriculum at SLB is not differentiated from public schools, so all subjects are applied as a whole. In learning, teachers use tools such as braille learning media, counting boards and abacus. For object recognition, children are given the opportunity to touch the object they want to be introduced. If the object cannot be touched, the teacher uses words.